STATISTICAL ANALYSIS OF THE MAIN INDICATORS IN EARLY EDUCATIONAL SYSTEM IN BACAU COUNTY COMPARED TO THE CENTRAL REGION OF THE REPUBLIC OF MOLDOVA - Ciomartan, Lacramioara (Studies and Scientific Researches. Economics Edition, 2019)
An important factor in promoting economic development is the educational capital that should be seen as an investment in those who will generate economic growth. The present paper aims to carry out a statistical analysis of indicators in the field of education: early education, presentation based on statistical indicators disseminated by the two main official institutions: the National Institute of Statistics of Romania and the National Bureau of Statistics of the Republic of Moldova. In order to quantify the educational phenomenon in the two territorial units for statistics regarding the education market, a rather small number of indicators were taken into account due to lack of their dissemination on the desired administrative-territorial units.